Application of an agr-Specific Antivirulence Compound as Therapy for Staphylococcus aureus-Induced Inflammatory Skin Disease. (4th May 2018) - Baldry, Mara; Nakamura, Yuumi; Nakagawa, Seitaro; Frees, Dorte; Matsue, Hiroyuki; Núñez, Gabriel; Ingmer, Hanne
Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease where more than 90% of patients affected are colonized with Staphylococcus aureus . In AD, S. aureus δ-toxin is a major virulence factor causing cutaneous inflammation via mast cell degranulation. δ-toxin is controlled by the S. aureus agr quorum sensing system, and thus we addressed whether interference with agr signaling would limit skin inflammation. Indeed, treatment of S. aureus with the agr -inhibitor solonamide B (SolB) abolished δ-toxin production and reduced skin inflammation in a mouse model of inflammatory skin disease, demonstrating the potential of antivirulence therapy in treating S. aureus -induced skin disorders.